2009
DOI: 10.1152/ajpheart.00338.2009
|View full text |Cite
|
Sign up to set email alerts
|

Calpain inhibition preserves myocardial structure and function following myocardial infarction

Abstract: Mani SK, Balasubramanian S, Zavadzkas JA, Jeffords LB, Rivers WT, Zile MR, Mukherjee R, Spinale FG, Kuppuswamy D. Calpain inhibition preserves myocardial structure and function following myocardial infarction. Am J Physiol Heart Circ Physiol 297: H1744 -H1751, 2009. First published September 4, 2009 doi:10.1152/ajpheart.00338.2009.-Cardiac pathology, such as myocardial infarction (MI), activates intracellular proteases that often trigger programmed cell death and contribute to maladaptive changes in myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 58 publications
(68 reference statements)
1
38
0
1
Order By: Relevance
“…Calpain activity is increased in the infarcted heart and in myocardia of patients with heart failure (9,10). Pharmacologic inhibition of calpain reduces ischemic cardiac injury and preserves cardiac structure after acute MI (11)(12)(13)(14). A recent study showed that calpain-1 knock-out reduced whereas calpain-1 overexpression enhanced myocardial injury and dysfunction within 4 days after coronary occlusion (15).…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 99%
“…Calpain activity is increased in the infarcted heart and in myocardia of patients with heart failure (9,10). Pharmacologic inhibition of calpain reduces ischemic cardiac injury and preserves cardiac structure after acute MI (11)(12)(13)(14). A recent study showed that calpain-1 knock-out reduced whereas calpain-1 overexpression enhanced myocardial injury and dysfunction within 4 days after coronary occlusion (15).…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 99%
“…These findings suggest that calpain-inhibition may still be a potentially useful therapeutic approach. Thus over-expression of calpastatin or use of exogenous calpain inhibitors has been shown to ameliorate or reduce: a) sepsisinduced muscle (diaphragm 122 and heart 123 ) weakness, b) post-MI cardiac muscle remodeling 124 , c) disuse atrophy 125 , and d) hyperglycemia-related cardiac muscle dysfunction 126 .…”
Section: Calpainsmentioning
confidence: 99%
“…At first it is beneficial, leading to continuing reduction of cardiac function and finally, after days and weeks, it causes heart failure (HF) [4,5]. Owing to the quantitative and qualitative changes in cardiomyocytes, LV contractile function is impaired after MI [6]. Many studies have shown that apoptosis (programmed cell death) of cardiomyocytes is one of the mechanisms leading to ventricular remodelling in animal models and human disease [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…One common mechanism of remodelling is hyper activation of caspase families. Activation of these proteases may cause disintegration of various key cellular proteins, thereby resulting in the loss of contractile proteins and hence reduction of cardiac muscle cell function [6].…”
Section: Introductionmentioning
confidence: 99%